2014
DOI: 10.3390/ijerph120100106
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond Green: Exploring the Relationship of Environment Type and Indicators of Perceived Environmental Quality on Emotional Well-Being following Group Walks

Abstract: Against the backdrop of increasing interest in the relationship between Nature and health, this study examined the effect of perceived environment type and indicators of perceived environmental quality on short-term emotional well-being following outdoor group walks. Participants (n = 127) of a national group walk program completed pre- and post-walk questionnaires for each walk attended (n = 1009) within a 13-week study period. Multilevel linear modelling was used to examine the main and moderation effects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 98 publications
(158 reference statements)
3
102
2
3
Order By: Relevance
“…Hansmann et al (2007) and Tyrväinen et al (2014) found only limited evidence that forests have a more positive influence on human health compared to designed city parks. Marselle et al (2015) even found no relationships between perceived naturalness and post-walk emotional well-being.…”
Section: Linkages Between Human Health and Landscape Quality Indicatomentioning
confidence: 91%
See 4 more Smart Citations
“…Hansmann et al (2007) and Tyrväinen et al (2014) found only limited evidence that forests have a more positive influence on human health compared to designed city parks. Marselle et al (2015) even found no relationships between perceived naturalness and post-walk emotional well-being.…”
Section: Linkages Between Human Health and Landscape Quality Indicatomentioning
confidence: 91%
“…In contrast, well-being was positively related to participants' perceived species richness (Carrus et al 2015;Dallimer et al 2012). However, Marselle et al (2015) found that a perceived high level of bird biodiversity correlated to a postwalk negative affect. Johansson et al (2014) presented images to analyse emotional and physiological responses to different states of biodiversity in temperate deciduous broad-leaf peri-urban forests in Sweden.…”
Section: Linkages Between Human Health and (Perceived) Biodiversitymentioning
confidence: 96%
See 3 more Smart Citations